Acquiring User Interface Design Skills through Experiential Learning - Mulimani, Deepa; Seeri, Shivananda V.; Patil, Prakashgoud R.; Kulkarni, Sujata (Journal of Engineering Education Transformations, 2025)
In these days of intuitive and intelligent software systems the audience is not going to put any effort into using the product, application or operating system - they'll expect it to be obvious. The perception of any software is driven entirely by its User Interface (UI). Usable software sells better and unusable software is abandoned. Designing usable UIs is challenging and instilling such designing skills in students is even more challenging. This paper investigates Experiential Learning methodology used to imbibe UI Designing Skills in students through the course "Principles of User Interface Design". The primary objective was to attain Graduate Attributes/Program Outcomes (POs) 1, 2 and 3 as defined in the Outcome Based Education (OBE). The approach comprised of two main activities- Identifying Good UIs and Bad UIs and Designing UI Prototypes. A rubric based assessment was used to test the concepts' realization among students. Though this novel approach did not claim to have given students deeper knowledge in UI designing, it did aim for a useful foundation. The approach can be adopted in designing good UIs in mini projects and capstone projects.